2010
DOI: 10.1097/meg.0b013e32832e9d6b
|View full text |Cite
|
Sign up to set email alerts
|

5-HTTLPR and STin2 polymorphisms in the serotonin transporter gene and irritable bowel syndrome: effect of bowel habit and sex

Abstract: Our finding that male IBS-D patients have a reduced frequency of the 5-HTTLPR (ss) genotype contradicts three earlier studies of a similar size, which did not take sex into account. Therefore, replication studies in even larger cohorts, stratifying for sex and endophenotypes, after assessing physiological and psychological traits, are required to unravel the contribution of SERT polymorphisms to the IBS phenotype.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 31 publications
2
28
0
1
Order By: Relevance
“…The 10/12 genotype has been associated with IBS in one study (114). However, at least five other studies found no association between STin2 VNTR and IBS (65,73,88,90,121).…”
Section: Neurotransmitter Mechanismsmentioning
confidence: 95%
See 1 more Smart Citation
“…The 10/12 genotype has been associated with IBS in one study (114). However, at least five other studies found no association between STin2 VNTR and IBS (65,73,88,90,121).…”
Section: Neurotransmitter Mechanismsmentioning
confidence: 95%
“…While the prevalence of IBS in India appears to be higher in men than in women (43), it is unclear why sex would explain the association of the SS genotype (for a gene located on chromosome 17, rather than an X or a Y chromosome) with C-IBS. A study that included patients with IBS from Germany and the United Kingdom [where prevalence is ϳ1.3-1.5:1 in women compared with men (38,47)] showed a lower prevalence of the SS genotype in IBS and, particularly, in diarrhea-predominant IBS (D-IBS), but this was only observed in male patients (34 male IBS patients and 30 male controls) (88).…”
Section: Neurotransmitter Mechanismsmentioning
confidence: 99%
“…The LL genotype has also been associated with constipationpredominant IBS (C-IBS) [11], whereas the ss genotype has been associated with increased IBS incidence in women [12] and with C-IBS [5]. Interestingly, many studies do not associate SERT polymorphism with IBS [9,13,14], whereas a recent study suggests that male D-IBS patients have a reduced frequency of the 5-HTTLPR ss genotype [15].…”
Section: Introductionmentioning
confidence: 99%
“…Three studies have examined another SERT gene polymorphism, designated as STin2 (located in intron 2 and consisting of a variable number -usually 9, 10 or 12 -of nearly identical 17bp repeats), for which any association with IBS or its clinical variants was not found (undetermined ethnicity, 26 [61][62][63]. In addition, Kohen et al [62] extended their search to 179A>G (currently 1936A>G), a SNP located immediately upstream of 5HTTLPR with opposite effects on SERT expression, showing a positive association of the G allele with IBS.…”
Section: Serotoninmentioning
confidence: 99%